CONVERSATIONAL IMPLICATURE IN ENGLISH LISTENING COMPREHENSION - Turnip, Tiur Dosmaria; Sinaga, Feni Agnes; Nasution, Jamaluddin (English Language Teaching Prima Journal (ELT), 2023)
There are some English learners feel hard in understanding a sentence when they are tested in listening comprehension. It can be seen when they are joining a test about English conversation although they have learned English Vocabulary and English Grammar. To increase the English learners’ listening comprehension ability, it is so necessary to introduce basic theories of Pragmatics to the English learners. Conversational Implicature theories by Grice is one of the most important aspects from the Pragmatics theories. Conversational Implicature by Grice focused on the phenomenon theory of conveying more than what have been explained in the theory. That is why, English learners as English listeners in this situation must be able to master the conversational implicature theory that already explained by Grice. It was about how to infer the implicature in guiding English learners’ learning and it is able to be learned in such theories in listening comprehension. This research attempted to examine the correlation between them and it stated the role played in the conversational implicature in listening comprehension.